Development of Efficient Callus Initiation of Malta (Citrus sinensis) Through Tissue Culture (International Journal of Agricultural Research, Innovation and Technology, 2013)
The effects of different hormonal concentration on shoot formation and callus induction were studied on BARI Malta-1 (Citrus sinensis). Seeds containing seed coat and without seed coat was treated by Murashige and Skoog (MS) media supplemented with 6-benzyl adenine (BA) and Kinetin (KIN). Removal of seed coat showed an early response for shoot formation. The highest (70%) shoot formation was obtained from seeds without seed coat treated with MS basal media + BA 1.0 mg/l while KIN showed no response for shoot formation in any supplemented concentration. However, in case of callus induction internodes and apical shoot tips were used as explants and 2, 4-dichlorophenoxy acetic acid (2, 4-D) was used as callus inducing hormone. MS basal media supplemented with 2, 4-D, 2.0 mg/l showed highest (68%) callus induction. DOI: http://dx.doi.org/10.3329/ijarit.v1i1-2.13935 Int. J. Agril. Res. Innov. & Tech. 1 (1&2): 64-68, December, 2011